Regulasi Keagamaan terhadap Aktivitas Rekreatif: Studi Empiris tentang Permainan Domino, Moralitas Sosial, dan Norma Masyarakat - Zainuddin Karim; Aswar Aswar; Abd. Raziq; Abd. Rahman Hidayat; Haidir Ali (IAI DDI Mangkoso, 2026)
The prohibition of playing dominoes in Kabuloang Hamlet reflects the strong influence of religious values and communal morality within a rural society. This study aims to examine the meaning of the prohibition and the role of religious and moral values in shaping collective norms. A qualitative descriptive approach was employed through observations and in-depth interviews with religious leaders, community figures, youth, and local residents. The findings reveal that the prohibition is not intended to restrict recreation, but rather serves as a preventive measure to avoid gambling practices (maysir), maintain religious discipline, and preserve social order. Religious values provide normative legitimacy, while social morality functions as a collective control mechanism. Religious and community leaders play a key role in sustaining this norm through persuasive approaches and moral example. This study concludes that the prohibition of playing domino cards represents a form of local wisdom aimed at maintaining moral stability in the community.